Integrated Logging, Production, and Geological Analysis for Bypassed Oil Identification in CNA Field, Central Sumatra Basin - Karina Larasati; Dimas Suryo Wicaksono; Dedi Kristanto; Hariyadi; Rahajeng Suryo Rahmadhini; Carin Nova Azzaria (Scientific Contributions Oil and Gas, 2026)
The Central Sumatra Basin’s CNA Field has been producing hydrocarbons since 1974 and is now considered a mature oil field. The field contains six Long Term Closed (LTC) wells and two Plug and Abandonment wells, providing an opportunity to enhance hydrocarbon recovery by identifying and reactivating residual productive zones. The study is based on two LTC wells, CNA-01 and CNA-03, which are suspected to contain bypassed oil potential. Integrated evaluation of wireline logging data, production history, and geological correlation was performed to identify prospective bypassed oil zones. As a first step in the analysis, resistivity and permeability cut-off values were determined, followed by qualitative log interpretation to identify hydrocarbon-bearing intervals. The identified zones were then confirmed using production test data, structural correlation, and historical production performance. Moreover, Chan’s Diagnostic Plot was used to analyze the water production behavior and to identify the dominant water influx mechanism. Results indicated a total of nine potential bypassed oil intervals, with five intervals identified in well CNA-01 and four intervals identified in well CNA-03, within the BKA and BKB sand units. The main factors affecting bypassed oil are reservoir heterogeneity, variation in vertical permeability, channeling and discontinuous sand distribution. The integrated analysis suggests several workover strategies, including additional perforation in uncompleted hydrocarbon-bearing zones, reducing intervals affected by excessive water production, and squeeze cementing to isolate non-productive intervals. The results presented here demonstrate the value of integrated reservoir evaluation in identifying remaining hydrocarbon potential and aiding mature field redevelopment.